A Mixed Method Study On The Examination Of Instructor Self-Efficacy Perception And Views In Flipped Learning - Ã‡ay, Tolga (ZAHRA: Research and Tought Elementary School of Islam Journal, 2022)
The aim of this study is to examine the self-efficacy perceptions of lecturers in flipped learning and opinions of prep school lecturers about their self-efficacy in flipped learning. Convergent parallel design, one of the mixed research methods, is employed in the study. The study group consists of 31 Turkish lecturers who work at the School of Foreign Languages at Ã‡aÄŸ University. The quantitative data of the research was obtained through the Flipped Learning Teacher Self-Efficacy Scale. Qualitative data was collected by open-ended questions form developed by the researcher. As a result of the study, it was concluded that the flipped learning self-efficacy perceptions of the preparatory school lecturers were at a high level. In addition, the lecturers stated in their views that their self-efficacy in flipped learning and technology use was at a certain level, but they have to continuously improve.